Scanning electron microscopic evaluation of microgap size in Morse taper implants with straight and angled abutments - Costa, Mariana Bispo; Ferreira, Lorena Fernandes; Marqueti, Antonio Carlos; Takeshita, Wilton Mitsunari [UNESP]; Trento, Cleverson Luciano (My University, 2022)
The aim of this study was to compare the sizes of the implant-abutment microgap in Morse taper implants with a straight abutment (ISA group) and Morse taper implants with an angled abutment (IAA group). A total of 19 Morse taper dental implants (3.8 . 11.0 mm) were used with their respective abutments; 10 abutments were angled at 20°, and 9 were straight. The implant-abutment units were immersed in an epoxy resin to form a base and then crosssectioned until about 50% of the volume was removed. The specimens were analyzed under a scanning electron microscope, and the size of the microgap was measured at 3 regions on each side of the implant, for a total of 6 measurements per specimen. Mann-Whitney U and Kruskal-Wallis tests were used for statistical analysis. In the ISA group, there were no statistically significant differences in the median sizes of the microgap at the different regions of the interface (P > 0.05; Kruskal-Wallis test). The mean (SD) values of the largest and smallest microgaps in the ISA group were 1.64 (1.38) and 0.83 (0.41) μm, respectively. In the IAA group, there was a statistically significant difference in the median sizes of the microgaps at the upper and middle regions on the left side (P = 0.031; Kruskal-Wallis test). The mean (SD) values of the largest and smallest microgaps were 1.43 (0.062) and 0.61 (0.27) μm, respectively. Comparison of the different regions in the ISA and IAA groups revealed that the only statistically significant difference was at the lower region on the right side (P = 0.027; Mann-Whitney U test). The sizes of the microgaps in the ISA and IAA groups were statistically similar in an overall analysis (P > 0.05; Mann-Whitney U test); however, the IAA group showed greater sealing ability. In addition, in both groups in vitro titanium oxide formation was observed at the interface, characterizing a type of coldweld joint that provides effective implant-abutment sealing.
Keywords: dental abutments; dental implants; scanning electron microscopy